Determination of the Acoustical Performance of Multipurpose Music Classrooms - Aslan, Ahmet; Oktav, Akin; Metin, Buket (Taylor & Francis Ltd, 2022)
It is important to analyse the multipurpose music classrooms (MMCs), where active teaching and music practice are held in the same space, with an eligible acoustical parameter set. In the current study, three different operational conditions (OCs) are introduced to determine such a parameter set, which includes T30, EDT, D50, C80, and STI. The aim of the study is to outline the acoustical performance of the MMCs according to the OCs. The acoustical performance of three MMCs located in three different schools is investigated. For the experimental component of the study, impulse response tests are conducted in the MMCs. The computational analysis incorporates the construction of 3D models of the MMCs. To cope with the epistemic uncertainties, a model update study is performed by synthesizing the experimental and computational outcomes. The results of the updated models are then compared to the regulations and the relevant studies available in the literature.
Metin, Buket/0000-0001-7539-7776;
Keywords: Architectural Acoustics; Computational Acoustics; Model Update; Multipurpose Music Classroom; Operational Conditions; Acoustical Parameters